Pengembangan Penggunaan Website Menara Terhadap Pemahaman Mengenai Nabi dan Rasul di SD Babakan Hurip Kelas IV - Nugroho, Bagas Adi; Nadila, Siti; Rouffiani, Syifa; Aeni, Ani Nur (An Naba, 2024)
This research is a development of learning media in the form of a website "MENARA (Mengenal Nabi dan Rasul)" to enhance elementary school students' understanding of Nabi and Rasul. The research method employed is Design and Development (DND) along with the application of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The study involved teachers and 4th grade students from Babakan Hurip Elementary School in the Sumedang regency as research subjects. An interactive website titled "MENARA" was developed with content focusing on introducing Nabi and Rasul in Islam, tailored to the elementary school curriculum. The website was designed with an engaging design approach and is easy to comprehend for children. The research findings indicate that the use of the "MENARA" website significantly improves students' understanding of Nabi and Rasul. Both student and teacher responses show that the designed product can be categorized as excellent. These findings demonstrate that website development using the DND approach and the application of the ADDIE model is an effective method in enhancing students' understanding of religious material, particularly the introduction of Nabi and Rasul in Islam. The implications of this research provide support for internet technology-based learning approaches in the context of religious education in elementary schools.